The Conceptual Framework of Information Technology Adoption Decision-making in a Closed-loop Supply Chain - Gan, Shu-San (International Journal of Supply Chain Management, 2019)
Closed-loop supply chain has gained a significant attention during the recent decades since there is an increased awareness toward sustainable development. However, the implementation of closed-loop supply chain is confronted with numerous barriers and challenges due to uncertainties in input as well as in process. In contrast to manufacturing process where the input is mostly homogeneous raw material, the reverse chains input comes from products end-of-use or end-of-life; therefore the timing, quality and quantity are uncertain. The recovery process also brings other challenges due to various quality grades of the product returns and various recovery options. On the other hand, information technology has been studied extensively in relation to supply chain management. Most of the works show that the use of information technology could enhance supply chain performance. However, the study on the importance of information technology in closed-loop supply chain is still limited. In this paper, we discuss the role of information technology and then propose a conceptual framework of decision making in adopting IT in closed-loop supply chain management.